"Second Line to Bury White Supremacy": Take 'Em Down Nola, monument removal, and residual memory. Issue 1 (2nd January 2020) - Maxson, J. David
ABSTRACT: As Lost Cause statues come down across the country, communities are forced to reckon with monumental absences. While the rhetorical significance of monuments is well-established in scholarly literature, the rhetoric of monumental absence is not as thoroughly covered. To better understand the role that monumental absence plays in both public space and civic life, this essay theorizes residual memory as the remaining rhetorical potency that clings to a commemorative site after the focal object or structure of memorialization is removed. To demonstrate the theoretical utility of residual memory and contribute to ongoing public debates about Lost Cause monuments, this essay uses rhetorical field methods to conduct a rhetorical analysis of Take 'Em Down NOLA's "Second Line to Bury White Supremacy." The secretive night time removal of the Liberty Place Monument in New Orleans on April 24, 2017 and the activist celebration that followed two weeks later provide an exemplary case for exploring how residual memories can be used to resist and revise regressive practices of public memory.